Integrating Social Intelligence Into Character-Based Education: A Contextual Learning Model in Modern Boarding Schools - Sabaruddin; Rusli Yusuf; Misri A. Muchsin; Masrizal (Emerging Science Journal, 2025)
Objectives: This study designs and evaluates a social intelligence-based learning model for social studies in modern Islamic boarding schools (pesantren) in Indonesia, addressing the lack of social-emotional integration in faith-based curricula. Methods/Analysis: A mixed-methods approach involved 150 participants from five pesantren, including students, teachers, and school leaders. Qualitative data were gathered via interviews, observations, documentation, and FGDs, while quantitative data were collected using a validated 25-item Social Skills Questionnaire. Descriptive statistics, paired-sample t-tests, and Cohen’s d assessed effectiveness, with methodological and theoretical triangulation ensuring qualitative validity. Findings: The model—integrating social values, interactive strategies, contextual materials, authentic assessment, and teacher facilitation produced significant gains in social intelligence. Problem-solving and tolerance improved most (+1.7 points each), and student participation rose from 42% to 88%. Both students and teachers reported high satisfaction with the collaborative, contextually relevant approach. The questionnaire demonstrated high reliability (Cronbach’s α = 0.87). Novelty/Improvement: This study introduces a culturally grounded, faith-based pedagogical framework embedding social intelligence into character-based education. By aligning Islamic values and Acehnese wisdom with 21st-century social competencies it provides a replicable model for enhancing social-emotional learning in similar educational contexts.